2020
DOI: 10.3389/fpsyg.2019.03074
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying in the University Setting. Relationship With Emotional Problems and Adaptation to the University

Abstract: Little scientific attention has been paid to the problem of cyberbullying in the university environment, compared to similar studies conducted on adolescents. This study attempts to analyze the predictive capacity of certain emotional problems (anxiety, depression, and stress) and university adaptation with respect to cyberbullying in victims and aggressors. The European Cyberbullying Intervention Project Questionnaire, the Depression Anxiety Stress Scale-21 and the Student Adaptation to College Questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 53 publications
(87 reference statements)
1
21
1
6
Order By: Relevance
“…Previous research suggested that cyberbullying perpetration is significantly associated with depression, and anxiety seems to partially or fully mediate this relationship in both clinical and non-clinical populations [ 25 , 26 ]. High levels of depression and stress were found to increase the probability of being both a cyberbullying victim as well as a cyberbullying perpetrator [ 27 ]. Furthermore, cyber victims and cyber aggressors seem to have similar levels of depression [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggested that cyberbullying perpetration is significantly associated with depression, and anxiety seems to partially or fully mediate this relationship in both clinical and non-clinical populations [ 25 , 26 ]. High levels of depression and stress were found to increase the probability of being both a cyberbullying victim as well as a cyberbullying perpetrator [ 27 ]. Furthermore, cyber victims and cyber aggressors seem to have similar levels of depression [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that those students who were victims, compared to those who were not, considered, to a greater extent, leaving their studies, with variables being related to social integration, such as receiving support from friends and professors also having a moderating effect. The study by [30] analyzed the predictive capacity of certain emotional problems (anxiety, depression, and stress) and the ability to adapt to university with respect to cyberbullying in 1282 Spanish university students. The results showed that high levels of depression and stress increased the probability of being a victim of cyberbullying, while high levels of depression increased the probability of being a cyberbully.…”
Section: Cyberbullying and The Ability To Adapt To Universitymentioning
confidence: 99%
“…Although previous empirical evidence has highlighted the relationship between cyberbullying and several educational variables such as academic motivation and learning strategies [16,18,19], the ability to adapt to university [29,30], and academic performance [34][35][36], there is a lack of studies that specifically examine the relationship between cyberbullying and such educational variables in university students. Therefore, the aim of this research is twofold: (1) to study the differences between the different roles involved in cyberbullying (victims, bullies, victimized bullies) and those uninvolved in it with respect to motivation and learning strategies, the ability to adapt to university, and academic performance; and…”
Section: The Present Studymentioning
confidence: 99%
“…Thus, many become cyberbullies by themselves in the future to reciprocate. Emotional problems have been reported as a highly influencing factor to become a cyberbully [60]. It has been widely reported that those individuals, who are having emotional problems like depression, anxiety & stress are mostly involved in cyberbullying behaviour [23].…”
Section: Level Of Griefmentioning
confidence: 99%